Social Aspects of Crisis Effects on Households: The Case of Ukraine - Larysa Krasnikova; Olena Osinkina; Tamara Podvysotskaya; Yuriy Podvysotskiy (The Vienna Institute for International Economic Studies (wiiw), 2012)
The paper investigates the effect of crisis on households' welfare and severity of poverty in Ukraine. We use Ukrainian Household Survey for three years – 2006, 2009, and 2010 that allows us to investigate separately economic conditions before, during and after the crisis. Welfare in our paper is measured by total income and total expenses per equivalent member; poverty is measured using an income and expenses approach, three different poverty lines are investigated. Most welfare and poverty determinants change over time, as the economic situation changes, although such determinants as education and work experience are equally important in all periods. Residents of Kyiv earn and spend, on average, by 9-11% more than residents of the rest of the country. Based on empirical results some policy recommendations were suggested family-support policies, support for small business, subsidizing new job-creation, healthy life-style support policies, public investment into child day-care facilities, and improvement of job-matching and professional training.
Keywords: D10; I32; O15; 330; Welfare function; poverty; transition; survey; Ukraine; financial crisis